The Problem of Squatters and Unmanaged Settlers in Nepal: More Effort, Fewer Solutions - Dahal, Lila Nath (KMC Research Journal, 2024)
The issue of squatters, landless individuals, and unmanaged settlements in Nepal is a long-standing and complex challenge that has persisted for decades. Despite numerous government initiatives and the establishment of various commissions, the problem remains unresolved, exacerbated by political instability, lack of implementation, and insufficient coordination among stakeholders. Squatters, defined as individuals without land or reliable income, have often resorted to occupying public or government land, leading to disputes, social instability, and hindered development. Past efforts to address this issue, including land distribution programs and legislative measures, have been largely ineffective due to weak enforcement and politicization.This paper examines the historical background, socio-economic context, and evolving definitions of squatters and unmanaged settlers, along with the strategies employed to manage the problem. It highlights key challenges such as encroachment, social conflict, and inequitable land distribution, while analyzing the shortcomings of past commissions tasked with resolving these issues. Despite distributing limited land to squatters and freed laborers, these efforts have often failed to achieve sustainable economic or social outcomes, perpetuating the cycle of unmanaged settlements.The persistence of these problems underscores the need for better governance, long-term planning, and the establishment of transparent, accountable mechanisms. Without addressing the root causes, including equitable land reform and infrastructural development, the issue of squatters and unmanaged settlements will continue to undermine Nepal’s socio-economic progress.